Experimental Validation of an Analytical Program and a Monte Carlo Simulation for the Computation of the Far Out-of-Field Dose in External Beam Photon Therapy Applied to Pediatric Patients - De Saint-Hubert, Marijke; Suesselbeck, Finja; Vasi, Fabiano; Stuckmann, Florian; Rodriguez, Miguel; Dabin, Jérémie; Timmermann, Beate; Thierry-Chef, Isabelle; Schneider, Uwe; Brualla, Lorenzo (Frontiers in Oncology, 2022)
Background: The out-of-the-field absorbed dose affects the probability of primary second radiation-induced cancers. This is particularly relevant in the case of pediatric treatments. There are currently no methods employed in the clinical routine for the computation of dose distributions from stray radiation in radiotherapy. To overcome this limitation in the framework of conventional teletherapy with photon beams two computational tools have been developed, one based on an analytical approach and another depending on a fast Monte Carlo algorithm. Materials and methods: An anthropomorphic phantom representing a 5-year-old child (ATOM, CIRS), was irradiated for a brain tumor using a Varian TrueBeam linac. Two treatments for the same planned target volume (PTV) were considered, namely, intensity-modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT). In all cases, the irradiation was conducted with a 6 MV energy beam using the flattening filter. The phantom had natLiF:Mg, Cu, P (MCP-N) thermoluminescent dosimeters (TLDs) in its 180 holes. To calculate the out-of-field dose an analytical algorithm was implemented to be run from a Varian Eclipse treatment planning system. The fast Monte Carlo code DPM was also used for computing the out-of-field dose. It was executed from the dose verification system PRIMO. Results: In the out-of-the-field region the absorbed dose was on average four orders of magnitude lower than the dose at the PTV. For the two modalities employed the discrepancy between the central values of the TLDs located in the out-of-the-field region and the corresponding positions in the analytic model were in general less than 40%. The discrepancy in the lung doses was more pronounced for IMRT. The same comparison between the experimental and the Monte Carlo data yielded differences, in general, smaller than 20%. It was observed that the VMAT irradiation produces the smallest out-of-the-field dose when compared to IMRT. Conclusions: The proposed computational methods for routine calculation of the out-of-the-field dose produce results that are similar, in most cases, with the experimental data. It has been experimentally found that the VMAT irradiation produces the smallest out-of-the-field dose when compared to IMRT for a given PTV.